Peningkatan Kemampuan Mengenal Huruf Hijaiyah Peserta Didik Kelas Tiga SD N Meles Adimulyo Melalui Media Genius Card - Azizah, Feti Laelatul; Fatimah, Siti (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2022)
This study aims to determine the increase in students' ability to recognize hijaiyah letters on media genius cards for grade 3 SD N Meles Adimulyo. This research is a classroom action research conducted in two cycles, each cycle consisting of two meetings. Each cycle consists of stages of planning, implementation, observation, and reflection. The research subjects were third grade students of SD N Meles Adimulyo. Data collection techniques using observation, interviews, documentation, and tests. The validity of the data using the tringulation technique. The results of the analysis show that as many as 58% of students get a complete score in learning hijaiyah letters with genius cards. Meanwhile, in the second cycle, 89% of students got a complete score in recognizing hijaiyah letters with genius card media. So it can be concluded that there is an increase in recognizing children's hijaiyah letters with genius card media.